Domestic Violence in Ghana: An Initial Step - Ofei-Aboagye, Rosemary Ofeibea (Columbia Journal of Gender and Law, 1994)
This Article focuses on and attempts to expose the anxiety of abused women in Ghana. This project is ambitious in that it names, isolates, and defines domestic violence within Ghanaian culture. This Article is divided into three sections. The first section focuses on the need to do research on domestic violence in Ghana. The second section addresses the “invisible” nature of domestic violence in Ghana and some of the possible reasons for this invisibility. The third section looks at the ways in which domestic violence could be examined and addressed in Ghana. While there is no clear-cut definition of domestic violence in Ghana, it is important to identify the fact that the phenomenon exists.